Performance of the South American Defense Council Under Autonomy Pressures. (25th November 2018) - Mijares, Víctor M.
Abstract : This article evaluates the performance of the South American Defense Council, based on the rational institutional design and the concept of the operability of alliances. The trajectory of the Council between 2009 and 2018, is examined through a theoretical approximation inspired by neoclassical realism and by applying the descriptive inference method of process tracing. The results indicate that in almost a decade, the Defense Council of the Union of South American Nations did not achieve full operability according to its institutional design. The evidence suggests that aspirations of national autonomy undermined the regional security autonomy project. The article affirms that the presence of a South American security regionalism problem resulting from national and regional autonomy tensions generated a paradox of autonomy.